Search for high-mass resonances decaying to a jet and a Lorentz-boosted resonance in proton-proton collisions at s=13TeV - Tumasyan, A. (2022)
A search is reported for high-mass hadronic resonances that decay to a parton and a Lorentz-boosted resonance, which in turn decays into a pair of partons. The search is based on data collected with the CMS detector at the LHC in proton-proton collisions at s=13TeV, corresponding to an integrated luminosity of 138fb−1. The boosted resonance is reconstructed as a single wide jet with substructure consistent with a two-body decay. The high-mass resonance is thus considered as a dijet system. The jet substructure information and the kinematic properties of cascade resonance decays are exploited to disentangle the signal from the large quantum chromodynamics multijet background. The dijet mass spectrum is analyzed for the presence of new high-mass resonances, and is found to be consistent with the standard model background predictions. Results are interpreted in a warped extra dimension model where the high-mass resonance is a Kaluza–Klein gluon, the boosted resonance is a radion, and the final state partons are all gluons. Limits on the production cross section are set as a function of the Kaluza–Klein gluon and radion masses. These limits exclude at 95% confidence level models with Kaluza–Klein gluon masses in the range 2.0 to 4.3 TeV and radion masses in the range 0.20 to 0.74 TeV. By exploring a novel experimental signature, the observed limits on the Kaluza–Klein gluon mass are extended by up to about 1 TeV compared to previous searches.